Electro-chemical deposition of nano hydroxyapatite-zinc coating on titanium metal substrate - N. A. El-Wassefy; F. M. Reicha; N. S. Aref (SpringerOpen, 2017)
Abstract Background Titanium is an inert metal that does not induce osteogenesis and has no antibacterial properties; it is proposed that hydroxyapatite coating can enhance its bioactivity, while zinc can contribute to antibacterial properties and improve osseointegration. Aims A nano-sized hydroxyapatite-zinc coating was deposited on commercially pure titanium using an electro-chemical process, in order to increase its surface roughness and enhance adhesion properties. Methods The hydroxyapatite-zinc coating was attained using an electro-chemical deposition in a solution composed of a naturally derived calcium carbonate, di-ammonium hydrogen phosphate, with a pure zinc metal as the anode and titanium as the cathode. The applied voltage was −2.5 for 2 h at a temperature of 85 °C. The resultant coating was characterized for its surface morphology and chemical composition using a scanning electron microscope (SEM), energy dispersive x-ray spectroscope (EDS), and Fourier transform infrared (FT-IR) spectrometer. The coated specimens were also evaluated for their surface roughness and adhesion quality. Results Hydroxyapatite-zinc coating had shown rosette-shaped, homogenous structure with nano-size distribution, as confirmed by SEM analysis. FT-IR and EDS proved that coatings are composed of hydroxyapatite (HA) and zinc. The surface roughness assessment revealed that the coating procedure had significantly increased average roughness (Ra) than the control, while the adhesive tape test demonstrated a high-quality adhesive coat with no laceration on tape removal. Conclusions The developed in vitro electro-chemical method can be employed for the deposition of an even thickness of nano HA-Zn adhered coatings on titanium substrate and increases its surface roughness significantly.